Inlays Made From a Hybrid Material: Adaptation and Bond Strengths - Bottino, M. A. [UNESP]; Campos, F. [UNESP]; Ramos, N. C. [UNESP]; Rippe, M. P.; Valandro, L. F.; Melo, R. M. [UNESP] (Operative Dentistry Inc, 2015)
The aim of this study was to evaluate the internal fit, marginal adaptation, and bond strengths of inlays made of computer-aided design/computer-aided manufacturing feldspathic ceramic and polymer-infiltrated ceramic. Twenty molars were randomly selected and prepared to receive inlays that were milled from both materials. Before cementation, internal fit was achieved using the replica technique by molding the internal surface with addition silicone and measuring the cement thicknesses of the pulpal and axial walls. Marginal adaptation was measured on the occlusal and proximal margins of the replica. The inlays were then cemented using resin cement (Panavia F2.0) and subjected to two million thermomechanical cycles in water (200 N load and 3.8-Hz frequency). The restored teeth were then cut into beams, using a lathe, for microtensile testing. The contact angles, marginal integrity, and surface patterns after etching were also observed. Statistical analysis was performed using two-way repeated measures analysis of variance (p<0.05), the Tukey test for internal fit and marginal adaptation, and the Student t-test for bond strength. The failure types (adhesive or cohesive) were classified on each fractured beam. The results showed that the misfit of the pulpal walls (p=0.0002) and the marginal adaptation (p=0.0001) of the feldspathic ceramic were significantly higher when compared to those of the polymer-infiltrated ceramic, while the bond strength values of the former were higher when compared to those of the latter. The contact angle of the polymer-infiltrated ceramic was also higher. In the present study, the hybrid ceramic presented improved internal and marginal adaptation, but the bond strengths were higher for the feldspathic ceramic.